Halosaur fishes (Notacanthiformes: Halosauridae) from Atlantic Spanish waters according to integrative taxonomy - Bañón, Rafael; Arronte, Juan Carlos; Armesto, Ángeles; Barros-García, David; Carlos, Alejandro De (Zootaxa, 2016)
From 2009 to 2011 thirty-five specimens belonging to six halosaurid species of the family Halosauridae were captured in two different locations in the northern waters of Spain. The specimens were identified as belonging to the genera Halosauropsis Collett, 1896, Halosaurus Johnson, 1864 and Aldrovandia Goode & Bean, 1896, including the following species: Halosauropsis macrochir (Günther, 1878), Halosaurus ovenii Johnson, 1864, Halosaurus johnsonianus Vaillant, 1888, Aldrovandia affinis (Günther, 1877), Aldrovandia phalacra (Vaillant, 1888) and Aldrovandia oleosa Sulak, 1977. The morphometric measurements and meristic characters of these specimens are given. As a result, a new northern limit of distribution of A. oleosa from the northeastern Atlantic is reported. Using a taxonomical integrative approach, the mitochondrial DNA COI gene sequences from all individuals where determined and their comparison with morphological characters showed no incongruities. Among these specimens, the highest genetic distance within species was 0.8% while the lowest value between species was 3.3%. This ample barcoding gap has allowed the delimitation and assignment of all species reported in a way that matches the traditional taxonomical methods previously employed.